A novel STS mutation and an Xp22.31 microdeletion in a Chinese family with X‐linked ichthyosis. (17th December 2020) - Huang, Y.; Luo, S.; Zhao, P.; Tan, L.; Fu, G.; Zhou, A.; He, X.
Abstract : Click here for the corresponding questions to this CME article.